1999
DOI: 10.1111/j.1151-2916.1999.tb02095.x
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure of Pristine and Solute‐Incorporated SrTiO3: III, Perfect‐Crystal, Grain‐Boundary Geometry, and Acceptor Doping

Abstract: Electronic structure is investigated for donor‐impurity‐incorporated perfect‐crystal and 36.8° symmetric tilt Sigma5 (310) grain‐boundary geometries of SrTiO3. The relaxed model of the atomic structure of the grain boundary used in the present investigations is the same as that used in Part II, as derived by Ravikumar et al. using lattice‐statics simulations based on pair‐potential calculations. As in Part II, the methodology of one‐electron first‐principle cluster calculations, which is discussed in Part I, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
8
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 27 publications
3
8
1
Order By: Relevance
“…Doping the crystal with Nb introduces Nb d states which are split between the valence and conduction bands. A similar result was found by Rodrigues et al [5] although in their case the Nb d valence states were located 8 eV below the Fermi energy while in this letter the impurity band is centred around 6 eV and is significantly broader. The Nb d and O p states are also hybridized as indicated by the computed overlap population of the Nb-O bond which is 0.66.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Doping the crystal with Nb introduces Nb d states which are split between the valence and conduction bands. A similar result was found by Rodrigues et al [5] although in their case the Nb d valence states were located 8 eV below the Fermi energy while in this letter the impurity band is centred around 6 eV and is significantly broader. The Nb d and O p states are also hybridized as indicated by the computed overlap population of the Nb-O bond which is 0.66.…”
supporting
confidence: 89%
“…There are, however, no first principles calculations which provide for deeper understanding of this behaviour. Rodrigues et al [5] have used the DV-Xα method to study Nb incorporation into the bulk and into the core of a [001] symmetric tilt boundary. However, they did not allow for atomic relaxation around the impurity and the model that they used for the tilt boundary structure was derived from an empirical pair potential calculation.…”
mentioning
confidence: 99%
“…They concluded that Nb as donor and Na as acceptor have the largest effect on the electrical conductivity. Rodrigues et al, 22 however, claimed the opposite for Nb doping in their embedded-cluster method study. In addition to the substitutions at cation ͑Sr, Ti͒ sites, Robertson 23 also discussed F, N, and S as substitutions for O using the results of tight-binding Green's-function method calculations.…”
Section: Introductionmentioning
confidence: 97%
“…Characterization of radiation-induced defects therefore becomes an important aspect of understanding the radiation response of this material. Meanwhile, theoretical investigations of SrTiO 3 have been performed to study defect formation and migration energies and stable defect configurations, using both empirical atomic simulations and first-principles calculations [14][15][16][17][18]. However, the dynamics of atomic processes in SrTiO 3 under irradiation are not yet well understood.…”
Section: Introductionmentioning
confidence: 99%